Pediatric Surgical Care During the COVID-19 Lockdown: What Has Changed and Future Perspectives for Restarting in Italy. The Point of View of the Italian Society of Pediatric Surgery - Morini, Francesco; Romeo, Carmelo; Chiarenza, Fabio; Esposito, Ciro; Gamba, Piergiorgio; Gennari, Fabrizio; Inserra, Alessandro; Cobellis, Giovanni; Leva, Ernesto; Angotti, Rossella; Raffaele, Alessandro; Cacciaguerra, Sebastiano; et al. (Frontiers in Pediatrics, 2022)
Background: Covid time exacerbated some of the conditions already considered critical in pediatric health assistance before pandemic. A new form of pediatric social abandonment has arisen leading to diagnostic delay in surgical disorders and a lack of support for the chronic ones. Health services were interrupted and ministerial appointments for pediatric surgical healthcare reprogramming were postponed. As a result, any determination to regulate the term of “pediatric” specificity was lost. The aim is, while facing the critical issues exacerbated by COVID-19 pandemic, to rebuilt future perspectives of pediatric surgical care in Italy. Methods: Each Pediatric Society, including, Italian Society of Pediatric Surgery was asked by the Italian Federation of Pediatric Associations and Scientific Societies to fill a questionnaire including the following the main issues: evaluation of pre-pandemic criticalities, pediatric care during the pandemic and recovery, current criticalities. The future care model of our specialty was analyzed in the second part of the questionnaire. Results: Children are seriously penalized both for surgical treatment as well as for the diagnostic component. In most centers the pediatric surgical teams have been integrated by the adult ones and specificity of training the pediatric operating nursing is in danger of survival. "Emotional" management of the child is absolutely not considered by the general management and the child has become again as adults patient of reduced size. Conclusions: A new functional pediatric surgical model needs to be established in general hospitals including activities for day surgery and outpatient surgery. A national health planning is needed for the Pediatric Surgery to support the care of fragile child